Sistema de proteção a pessoas ameaçadas de morte em Mato Grosso : do depoente especial aos programas de proteção - Silva, Marcia Cristina Ourives da (2016)
Brazil ratified the main global and regional instruments relating to the protection of human rights, as well as included and recognized several guidelines for the protection of these rights in the Constitution of 1988. This time, the overall objective of this study was to analyze how the state of Mato Grosso offers protection to threatened with death people when they seek state protection. Therefore, this study sought to draw a picture of the existing protection system, glimpsing the forms of protection and checking with public agencies and entities of civil society organizations, as is the protection of people threatened in the state. Finally, sought to verify the existence of the State Protection Network and what is its relationship with the National System of Protection of Threatened Persons. For this study endangered people are the victims, witnesses, children and adolescents threatened with death and human rights defenders, as discipline Brazilian and international law. The study analysis was characterized by observation with a qualitative approach and descriptive type, the exploratory, relying on a theoretical basis consistent through literature technique consists of the analysis of texts and published documents, including statistical data presented in meetings with the Presidency, the National Coordination Reports Protection Programs, Reports of the Federal Police, prosecutors and official documents available on the internet and other officially authorized. The Protection Program for Victims and Witnesses, human rights defenders and Child and Adolescent Death Threatened at the state level are extremely important, not only for the safety assurance of life of victims and witnesses, but together, the defense and promotion of all fundamental rights, ensuring that all victims and witnesses, human rights defenders and Children and Adolescents Threatened Death, quality of life and continuity of their work.